A Comparative Study of the Impact of teaching methods on Teaching Effectiveness and Pupils’ Skills Acquisition in Home Economics in Upper Basic Classes in Itu Local Government Area of Akwa Ibom State, Nigeria - Boniface Sunday AKPAN; Grace Effiong UDONGWO; Asuquo A. UTIN (International Journal on Orange Technologies, 2020)
The study examined the impact of teaching methods on Teaching Effectiveness and Pupils’ skills acquisition in Home Economics in Upper Basic Classes in Itu Local Government Area of Akwa Ibom State, Nigeria. A comparative survey design was adopted for the study. Purposive sampling technique was used to identify the schools that actively teach and practice Home Economics, while one hundred and Eighty-Four (184) teachers (110 Females, 74 Males) were used as respondents in the study, selected through stratified sampling technique. A 15-item Questionnaire tagged: “Teaching Effectiveness for Skills Acquisition in Home Economics Questionnaire (TESAHEQ)”, was used for data collection in the study, arranged in a 4-point Likert Scale of Strongly Agree (SA), Agree (A), Disagree (D) and Strongly Disagree (SD). The questionnaire was validated by one (1) experts in test and measurement and one (1) expert in home economics. Test-retest reliability index was used to ascertain the reliability of the Questionnaire and it produced a reliability coefficient of 0.88, proving the instrument reliable enough for use in the study. Two research questions and 2 hypotheses were formulated to guide the study. Descriptive statistics of mean was used to answer the research questions. Independent T-test was used to test the hypothesis formulated at 0.05 level of significance. The findings in the study revealed that learner-centered methods of teaching such as discussion, guided-demonstration, role-play, and dramatization method are highly effective in facilitating skills acquisition in pupils than teacher-centered method of teaching such as descriptive, lecture, demonstration/flipped classroom method. The result also proved a significant impact of Teaching Effectiveness on Pupils’ Skills Acquisition in Home Economics in Upper Basic Classes based on gender of the pupils. Based on the study, it was recommended among others that workshops, seminars and other modes of training be given to teachers to update their teaching skills for higher teaching effectiveness.